Różne aspekty wielokulturowości z perspektywy nauczyciela akademickiego. Dobre praktyki - Bogdanowicz, Izabela (Kultura-Społeczeństwo-Edukacja, 2016)
The article presents ten selected practises, which give good teaching results in student groups that include foreigners. Among good practices are proprietary solutions, such as specially designed team-work cards (tool), organisation of moderated discussions and organisation of work in teams (techniques). The author draws conclusions that are not supported by the research. However, they may have practical value for people who teach classes in multicultural student environment. Good practices, an outcome of author’s professional experience, may also serve as a starting point for discussion about multiculturalism in the student community. Identification of common problems, in conjunction with presentation of good practices, allows a flexible approach to the readers; leaves them space to develop their own solutions, according to the conditions.